MORPHOLOGICAL AND CHEMICAL CHARACTERISTICS OF VARIOUS PUMMELO (Citrus maxima (Burm.) Merr.) ACCESSIONS FROM MAGETAN REGENCY - Arifah Rahayu; Wini Nahraeni; Nur Rochman; Rizki Yora Ardiansyah (JURNAL AGRONIDA, 2017)
Magetan Regency was the production centre of pummelo that have many accessions  with various morphological and chemical characteristics, but only a few of them were identificated. This study was aimed at identifying morphological and chemical characteristics of pummelo fruits in Magetan Regency.  The study was conducted in the Biology Laboratory of Djuanda University, Bogor from May to July 2015.  Results showed with regard to their morphological characteristic, pomelo plants in this region were found to have spheroid and spheroid-pyriform fruits and the weight of their fruit parts, fruit core width, mesocarp thickness, fruit circle before peeling, fruit circle after peeling, number of fruit segments, number of developed seeds, and edible parts of the fruit were varied.  Chemical characteristics were also found to be varied with vitamin C content of 29.80−44.66 mg/100g, total soluble solids (TSS) content of 8.10−9.72°Brix, total titratable acidity (TAA) of 0.31−0.53 g/100 ml, and TSS/ TAA ratio of 17.69−28.58. Key words: production centre of pummelo, spheroid, vitamin C, TSS